Capacity Building of Forest Local Community, Tree Seeds Providers and Forestry Extension Workers on Plus Tree Selection Technique in Kediri, East Java, Indonesia - Siregar, Ulfah Juniarti; Nugroho, Aditya; Winata, Bayu; Sudrajat, Dede Jajat; Nurianti, Esti; Haneda, Noor Farikhah (Talenta Publisher, 2023)
Community forests play significant role in supplying national demand of woods, sustaining local ecosystem and increasing benefit for local community. Tree plantings for both community forests and rehabilitation of degraded forests and lands, however often neglect utilization of good quality seeds, which resulted in low quality of forest plantation. In order to support the procurement of good quality seeds, it is necessary to raise awareness of local community, seeds providers and forest extension workers on the production of good quality seeds through tree selection program. This paper reported the activity to build the capacity of local community, seeds providers and forest extension workers on plus trees selection, as sources of good quality seeds production. The training activity took place two times at Ngancar Village, Kediri Regency, East Java. The participants in each training received lectures in a classroom and hand-in practical work on tree selection techniques in the field. The topics given are considered as important by participants, as evident from the increasing number of participants in the second time of training. Analysis of pre- and post-test conducted showed that the participants knowledge and skill increased by 27,9 % after training, regardless of their ages and educational backgrounds.